PENGGUNAAN Bacillus ISOLAT LOKAL UNTUK MENEKAN PENYAKIT LINCAT TEMBAKAU TEMANGGUNG - Triwidodo Arwiyanto; Rahmad Asfanudin; Arif Wibowo; Toekidjo Martoredjo; Gembong Dalmadiyo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Lincat disease of temanggung tobacco could not be controlled effectively. One method of control which could be integrated with other measures is biological control. Bacillus is one of soil microorganisms which was not used widely as a biological control agent of plant disease. This report showed the results of the use of local isolates of Bacillus in controlling lincat disease of temanggung tobacco. As much as 91 isolates of Bacillus were directly tested in the field for their capability in suppressing lincat disease development. Six isolates, Ba-4, Ba-22, Ba-24, Ba-30, Ba-33, and Ba-41, could suppress lincat disease in the field. The result of in vitro test indicated that not all isolates which produced zone of inhibition in vitro could suppress disease development in the field. On the contrary, not all isolates which suppressed lincat disease in the field could inhibit the growth of pathogen in vitro. Isolate Ba-41, could suppressed lincat disease in the field and inhibited the growth of Meloidogyne incognita but not inhibited the growth of Ralstonia solanacearum.